2020
DOI: 10.3390/rs12071105
|View full text |Cite
|
Sign up to set email alerts
|

GHS-POP Accuracy Assessment: Poland and Portugal Case Study

Abstract: The Global Human Settlement Population Grid (GHS-POP) the latest released global gridded population dataset based on remotely sensed data and developed by the EU Joint Research Centre, depicts the distribution and density of the total population as the number of people per grid cell. This study aims to assess the GHS-POP data accuracy based on root mean square error (RMSE), mean absolute error (MAE), and mean absolute percentage error (MAPE) and the correlation coefficient. The study was conducted for Poland a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Large errors increase significantly when the population density and growth rate are higher than 610 persons/km 2 and 1.54% in this research, respectively. Similarly, another study also confirmed that the GHS-POP underestimates the population in densely populated regions [26]. Therefore, we appeal that the gridded population data producers would value highly the high population density and growth rate regions when they distribute the population.…”
Section: Suggestions For the Gridded Datasets' Producers And Userssupporting
confidence: 60%
See 1 more Smart Citation
“…Large errors increase significantly when the population density and growth rate are higher than 610 persons/km 2 and 1.54% in this research, respectively. Similarly, another study also confirmed that the GHS-POP underestimates the population in densely populated regions [26]. Therefore, we appeal that the gridded population data producers would value highly the high population density and growth rate regions when they distribute the population.…”
Section: Suggestions For the Gridded Datasets' Producers And Userssupporting
confidence: 60%
“…MSEA is experiencing rapid population changes with a high population growth rate and accelerating urbanization since the 1950s [25][26][27]. A two-decade (2000-2019) average of total population increment in Cambodia, Laos, Myanmar, Thailand, and Vietnam were 35.6%, 34.67%, 15.68%, 10.6%, and 20.71%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, similar to the accuracy assessment of any other RS thematic map, a comprehensive quantitative evaluation of population distribution grids should be based on independent and high-resolution ground-truth data, such as population numbers at the pixel level. However, due to the fact that these types of reference data hardly exist at large scales (e.g., they are only available for some countries) [21,56,57], or when they do exist are difficult to acquire due to privacy protection policies, a "true-validation" of continental and global gridded population distribution datasets is still not possible to implement.…”
Section: Quantitative Accuracy Assessmentmentioning
confidence: 99%
“…Because GHS-POP relies 265 on GHS-BUILT, for which detection in sparse and rural areas is lacking (Leyk et al, 2018), it may tend to overconcentrate population into built-up areas, overestimating the number of urban residents (depending on how urban areas themselves are delineated). GHS-POP has been shown in recent studies to produce the most accurate pixel-level population estimates when compared to local data for some locations, especially in urban areas (Archila Bustos et al, 2020;Calka and Bielecka, 2020). 270…”
Section: Ghs-pop 255mentioning
confidence: 99%